Injectable Hydrogel-Based Nanocomposites for Cardiovascular Diseases - Liao, Xiaoshan; Yang, Xushan; Deng, Hong; Hao, Yuting; Mao, Lianzhi; Zhang, Rongjun; Liao, Wenzhen; Yuan, Miaomiao (Frontiers in Bioengineering and Biotechnology, 2020)
Cardiovascular diseases (CVDs), including a series of pathological disorders, severely affect millions of people all over the world. To address this issue, several potential therapies have been developed for treating CVDs, including injectable hydrogels as a minimally invasive method. However, the utilization of injectable hydrogel is a bit restricted recently owing to some limitation， such as transporting the therapeutic agent more accurately to the target site and prolonging their retention locally. This review focuses on the advances in injectable hydrogels for CVD, detailing the types of injectable hydrogels (natural or synthetic), especially that complexed with stem cells, cytokines, nano-chemical particles, exosomes, genetic material including DNA or RNA, etc. Moreover, we summarized the mainly prominent mechanism, based on which injectable hydrogel present excellent treating effect of cardiovascular repair. All in all, it is hopefully that injectable hydrogel-based nanocomposites would be a potential candidate through cardiac repair in CVDs treatment.In the current years, cardiovascular diseases (CVDs) has been an urgent threat which heavily burdens people's health and economy on a global scale. At present, the main therapeutic strategy of treating CVDs are utilization of drugs and surgical operation. However, there exist some obstacle, including the poor targeting efficiency of agent along with severe side effect, and the risk of postoperative complications. Therefore, it is imperative to search for a new method in CVDs treatment. Recently, injectable hydrogels show great potential in CVDs therapy as a minimally invasive treatment. This review focus on the advances of injectable hydrogels (including natural and synthetic injectable hydrogels), especially those loaded with stem cells, carbon nanotubes, exosomes and others components which meet the requirement of novel nanomaterials in CVDs treatment. Furthermore, the review describes the main mechanisms of injectable hydrogel-based nanocomposites in treating CVDs. This review summarizes the latest advancement of injectable hydrogel-based nanotechnology in the past decades and points out the inferiority of current research.By and large, this review presents a new opportunity for the development of injectable hydrogels-based minimally invasive treatment for CVDs.